Path planning and simulation for two mobile robots - Sheng, Hao Ran (Nanyang Technological University, 2024)
The mobile robot developed over six decades. From its initial beginnings to its current state, mobile robots have become necessary companions in our daily lives, offering assistance and efficiency across lots of domains. As society progresses the role of robots becomes more and more important, with their abilities developing to complete complex tasks which once deemed exclusive to human intervention. In this project, we focus on designing a task for 2 mobile robots through path planning and simulation using the MATLAB and SIMULINK. Many kinds of algorithms can be used for path planning. What are their theories and how do we tune their parameters to make it more efficient in our task? In simulation, how the task subdivides into many small parts and how to assign those sub-task to 2 mobile robots and make 2 mobile robots corporate like human behavior.With technology learning and task execution, we can reveal the capacity of two mobile robots to collaborate seamlessly. We design such a landscape where 2 mobile robots adeptly navigate through a warehouse environment;, effectively sorting 3 kinds of packets and dispatching them to 3 designated areas without collision between 2 mobile robots or any predefined obstacles. Thus, our simulation not only highlights the technical prowess of mobile robots but also underscores their potential to adept various tasks in different environments.